A new medium for the detection of fluorescent pigment production by pseudomonads. (6th August 2012) - Lamichhane, J. R.; Varvaro, L.
Abstract : Two media (King's B [KB] and CSGA) commonly used for the detection of fluorescent pigment by Pseudomonas spp. were compared to a new medium proposed in this study, PGS agar. Thirty‐nine strains of 10 different species of Pseudomonas from several geographic regions were screened. The efficacies of these media were examined under several conditions, including the addition of iron‐binding substances or supplementation with extra iron. The medium developed, which included an iron‐binding agent, was the most permissive for production of fluorescent pigments when compared to KB and CSGA. Thirty‐seven of the 39 pseudomonad strains screened were highly fluorescent on this new medium compared to 15 and 16 strains, respectively, on KB or CSGA. The optimal composition of the medium per litre was Bacto peptone 10 g, gelatin 20 g, sucrose 20 g, agar 15 g, dipotassium hydrogen phosphate 1 g, magnesium sulphate heptahydrate 1 g and conalbumin 2 g. Protocol validation tests performed through an intra‐laboratory study in comparison to KB demonstrated the effectiveness of the new PGS medium.